Crossing the Democratic Boundaries? Israeli protest against the Autocratization Perils of the 2023 Institutional Reform - Helled, Alon (SocietàMutamentoPolitica, 2024)
In the absence of the written constitution, Israeli society is institutionally anchored to the twofold premise of being as equally Jewish as democratic, according to the 1948 Declaration of Independence. These two properties are the foundation stones of the country’s national habitus, the system of norms and codes interiorized by citizens. Yet, Israeli democracy has faced many challenges, both external (geopolitical conflicts) and internal (the ramifications of the Occupation of Palestinian Territories and the increasing messianism of its political religious parties). The latter have resulted in a process of seemingly unstoppable autocratization. The paper enquires the types of protest in Israel and delineates the uniqueness of the last wave of protest against the legal reform, promoted by Israel’s 37th government. The analysis thus contextualizes moments of democratic friction, inspired by the Bourdieusian concept of hysteresis. This is situated in light of Israeli historical repertoire of manifested moments of dissent. By juxtaposing the (inevitable) clash between the country’s Jewish exclusiveness and democratic republican universalism, the incompatibility between the two elements as the main factor of Israel’s democratic backsliding towards autocratization reveals its sociological reasons.